Escola Industrial de Jaú : contexto político-econômico da criação e os primeiros tempos (1939-1960) - Bertoni Junior, Lauriberto de Jesus (Universidade Federal de São Carlos, 2017)
The Joaquim Ferreira do Amaral Industrial School in Jau, since the first years of operation was designed to train the student for the imminent industrialization and urbanization of the city. Considering this aspect, the present study has as general objective to analyze its role as teacher of the student-worker until 1960, justifying the need to rescue the history of this educational institution, understanding it in its particularities and intentionalities. For this, the epistemological paradigm adopted was historical-dialectic, aiming at understanding society in a scientific perspective, in which man creates a relation with the environment in which he is inserted, and is responsible for interfering in him. The sources used were books, journals and scientific articles, completion papers, local and regional newspapers, photographs and reports of students, teachers and employees of the time. Thus, through the research, it was possible to analyze the representativeness of the Industrial School, seeking to unveil what it meant in the developmentalist reality of jauense, that is, analyzing the political and economic context of its creation and the earliest times. Place of implantation was intentional, as it met the national industrial proposals, which resulted in the great acceptance of the establishment throughout the region.
Keywords: Educação profissional; Escola Industrial de Jaú; Aluno-trabalhador; Professional education; Industrial School of Jau; Student-worker; CIENCIAS HUMANAS::EDUCACAO